The Zimbabwean Response to RENAMO Incursions: A Conflict Transformation Perspective (The Strategic Review for Southern Africa, 2021)
The study analysed the Zimbabwean responses to the RENAMO incursions that have aff ected communities along the border. The analysis was done through the lens of John Paul Lederach’s theory of Confl ict Transformation. In particular, the study sought to gauge the eff ectiveness and sustainability of these methods employed by both the Zimbabwean community and the government. The recurrence of the violent incursions necessitated the study into the Zimbabwean border communities by the RENAMO rebels. It was also necessitated by the recurrence of hostilities between RENAMO and FRELIMO forces in Mozambique. The study was based on the case study of Chipinge in Manicaland, Zimbabwe. The community is located near the Zimbabwe-Mozambique border and is frequently aff ected by violent incursions whenever confl ict breaks out in Mozambique. The research fi ndings made it clear that the Zimbabwean responses to the RENAMO incursions have not been eff ective. The responses thus far have left the border communities vulnerable to further attacks from the rebels. However, these approaches are unsustainable from a Confl ict transformation perspective. The approaches are short-sighted in outlook and have at best achieved a negative peace scenario. The study recommends Zimbabwe devise a conflict transformative approach that is long term in nature to stand against the RENAMO incursions eff ectively.